Effects of Carrier Gas Transport on the Structure and Performanc e of Al-doped ZnO Films Grown by Aerosol-Assisted Chemical Vapour Deposition Method - Wang, Lixin; Lu, Lin; Zhang, Liqian; Wang, Xiaojuan; Qin, Xiujuan (Current Nanoscience, 2017)
Background: Al-doped ZnO (AZO) films were successfully deposited on the glass substrates at temperature 400 by aerosol-assisted chemical vapour deposition method. Zinc acetate dihydrate, aluminum nitrate nonahydrate, methanol were used as a starting material and solvent, respectively. The influences of carrier gas (N2) flow rate on the structural, optical and electrical properties of grown AZO films were full investigated. The research results indicated that the growth orientation between polar and nonpolar faces in ZnO crystal exhibited obvious difference with increasing carrier gas flow rate. Additionally, carrier gas transport also had a great effect on crystal quality, surface structure and electrical properties of the sample. The uniform AZO film with the resistivity value of 6.7×10-3 Ω·cm and optical transmittance of 80% in the visible range was obtained at a suitable carrier gas flow rate of 30 L/h. Methods: AZO films were deposited on glass substrates in air at temperature 400 by the cold-wall AACVD technique. 0.1 M (mol/L) starting solution was prepared from zinc acetate [Zn(CH3COO)2·2H2O] and aluminum nitrate [Al(NO3)3·9H2O] dissolved in methanol, with a constant Al/Zn atomic ratio of 4 at.%. The reagents used in the experiments were analytical grade and utilized without further purification. The glass substrates were previously cleaned by appropriate solvents (detergent, water, methanol or acetone) and dried in air. Then they were placed into a cold-wall reaction chamber, where two clean parallel plates, 8 mm apart, were heated using a graphite block controlled by a thermostat monitored by a Pt–Rh thermocouple. The precursor solution of 35 ml was nebulized by an ultrasonic humidifier with a wave frequency of 1.7 MHz to form an aerosol mist within a glass bottle. The aerosol mist was transported by an inert gas (N2) to reaction chamber, where it evaporated and then the films deposited on the glass substrate. Carrier gas flow rate ranged from 20 L/h to 40 L/h. The substrates and films were allowed to cool to room temperature in situ and were stored in air. The film uniformity on the substrate at each end of carrier gas flow was different from the central area. Residual part of 70 mm was used for testing after cutting out 40 mm from two ends of the sample, respectively. Results: These researches mostly focused on the doping element, solvent, raw materials, concentrate, and temperature, etcetera. Carrier gas (N2) transport is also an important experimental parameter. The present work, therefore, reveals the mechanism of preferred growth orientation for faces was discussed by Fujihara theory and Boundary layer model in CVD system. In addition, the relationship between carrier gas transport and structure, optical and electrical characteristics of the AZO films were also discussed systematacially in the cold-wall AACVD system. Conclusion: In summary, the mass transport process of inert gas (N2) acted as a carrier in AACVD system has obvious effects on preferred growth orientation, crystal quality, surface structure and electrical properties of deposited films. The AZO films with different growth orientation can be obtained by only adjusting carrier gas flow rate. It has a great significance for preparing ZnO films application to different field. Based on boundary layer model, the appropriate carrier gas flow rate is beneficial to achieve high deposition rate and uniform coating film with excellent electrical properties together with light trapping structure. In this work, we fabricate the AZO film with (110) preferred growth orientation on the soda-lime glass substrates at a suitable carrier gas flow rate of 30 L/h. Meanwhile, deposited films have the resistivity value of 6.7×10-3 Ω·cm and optical transmittance of 80% in the visible range. It is a low cost and simple art, we believe the AACVD technique can potentially be used to fabricate a wider range of zinc oxide films with controlled growth orientation and morphology.
Keywords: gas transport